Working on Literacy in CLIL/Bilingual Contexts: Reading to Learn and Teacher Development - Rachel Whittaker; Claire Acevedo (Universidad de Navarra, 2016)
This paper describes a project implementing a literacy programme based on a linguistic approach to teaching reading and writing, found especially useful for subject classes taught through a foreign language. The programme, Reading to Learn (Rose, 2014; Rose & Martin, 2012), based on an analysis of the genres of different subjects, their language features and the diffi culties these pose learners, offers teachers an explicit and detailed method to approach text comprehension/production. The paper includes examples of texts from late primary to mid-secondary content classes as analysed and used by teachers, student texts, and reactions to the pedagogy.